Thrown to the (Were)Wolves: Sisterhood, Vengeance, and Liberal Feminism in Maggie Tokuda-Hall and Lisa Sterle’s Squad - Jessica Caravaggio (Humanities)
In Maggie Tokuda-Hall and Lisa Sterle’s graphic novel Squad, protagonist Becca and her new friends at Piedmont High are not human adolescents but a pack of werewolves who must kill to stay alive and select teenage boys—“the WORST ones” (70)—as their meal of choice. The power of the pack’s “monstrous” bodies is a dangerous privilege and responsibility that Squad suggests is often misused to victimize innocents. The book critiques individualistic Western/liberal feminism—an ideology also critiqued by contemporary feminist writers—that encourages women and girls to gain power for themselves and then use it to perpetuate hierarchies of domination. Through an analysis of the figure of the werewolf and fantasies of revenge, this article suggests that both Squad’s narrative and its comic images guide readers toward an understanding of how liberal feminist ideology impedes collective empowerment. This article ultimately argues that Squad can be wielded as a potential feminist consciousness-raising tool for teaching about the ethics of different feminist ideologies.